ASSOCIATION OF SERUM ALBUMIN LEVELS WITH AFP AND PIVA-II IN PATIENTS WITH HEPATOCELLULAR CARCINOMA - Muhammad Talha Asif; Shahzadi Javeed; Tayyab Khurshid; Sadia Ahmed Zuberi; Qandeel Abbas Soomro; Amirullah; Qambar Abbas; Muhammad Rizwan; Haseeb Khaliq (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Hepatocellular carcinoma (HCC) is one of the most common malignant tumors affecting the digestive tract, ranking fifth in morbidity and third in mortality among cancers globally, posing a severe threat to health and life. This study investigated whether serum albumin levels are associated with alpha-fetoprotein (AFP) and PIVKA-II in HCC patients. Conducted as an experimental study in the medical laboratory of Islamabad Diagnostic Center, Faisalabad, it involved the planned recruitment of 50 participants who provided written consent prior to sample collection. Patients were evaluated based on serum AFP, PIVKA-II, and other laboratory parameters. The findings from univariate logistic regression analysis revealed that the HCC group had significantly higher concentrations of AFP and PIVKA-II (p < 0.01). Additionally, a decrease in albumin levels (p = 0.056) was observed with increasing levels of AFP and PIVKA-II. The study concluded that there is a significant negative correlation between albumin levels and the levels of PIVKA-II and AFP in HCC patients, suggesting that lower albumin levels may indicate more severe liver disease and advanced disease progression. Furthermore, a positive correlation between AFP and PIVKA-II levels supports their combined use for diagnostic or therapeutic purposes.